포스트휴먼 시대와 의료문학 연구의 가능성: 불가코프의 『개의 심장』에 대한 실험적 연구 - 이병훈 (연세의사학, 2023)
Bulgakov‘s Heart of a Dog is a representative work of Russian satirical literature of the early 20th century and can also be said to be a masterpiece of “literature and medicine.” It would probably not be easy to find a work that embodies the connection between literature and medicine as realistically and profoundly as this work. In this respect, Heart of a Dog is the best example for examining the potential of research on literature and medicine. Similar to Heart of a Dog, most novels that explore literature and medicine have hidden plots (medical plot). This is often a plot that can only be reconstructed from the perspective of medical literature rather than what the author intended. The study of literature and medicine stems from an expansionary motive to connect the interpretation of literary works to the context of the history of medicine (and, broadly speaking, the history of science). This actively allows the involvement of scientific and medical knowledge in literary research. However, it is true that awareness of this problem has been neglected until now, and as the importance of science and medicine in our lives increases, there may be a need to evaluate this issue differently.
Keywords: Posthuman; literature and medicine; Bulgakov; Heart of a Dog; satire; 포스트휴먼; 의료문학; 불가코프; “개의 심장”; 풍자